Exploring the therapeutic potential and bioactive compounds in Pyrus species - Sonia Singh; Riya Verma; Himanshu Sharma (Elsevier, 2024)
Introduction: The genus Pyrus encompasses a diverse range of species the Chinese pear (Pyrus ussuriensis; Pyrus bretschneideri), Japanese pear (Pyrus pyrifolia), and the European pear (Pyrus communis) that have been extensively studied for their phytochemical constituents and associated pharmacological activities. Materials and Methods: This manuscript provides significant data regarding the phytochemistry and pharmacological impact of many species of Pyrus. The data was gathered from electronic repositories that included Science Direct, Web of Science, Scopus, and PubMed. Result and Conclusion: This review aims to provide a comprehensive overview of the bioactive compounds present in Pyrus species and their potential therapeutic applications. The phytoconstituents identified in Pyrus plants include a variety of phenolic compounds, flavonoids, triterpenoids, and organic acids. These phytochemicals contribute to the diverse pharmacological properties exhibited by Pyrus species, such as anti-inflammatory, antimicrobial, antioxidant, antibacterial, hepatoprotective and anticancer activities.